Autologous Stem Cell Transplantation in Testicular Germ Cell Tumor—Preliminary Experience from a Single Center - Selvarajan, Gangothri; Jayachandran, Perumal Kalaiyarasi; Rajan, Arun Kumar; Kesana, Sivashree; Kannan, Krishnarathinam; Sagar, Tenali Gnana; Ganesan, Trivadi Sundaram (South Asian Journal of Cancer, 2021)
Background Germ cell tumor (GCT) of the testis is one of the highly curable solid organ malignancies. Those who experience relapse after platinum-based chemotherapy can be salvaged with systemic therapy followed by high-dose chemotherapy (HDCT) and autologous stem cell transplantation (ASCT). Complete remission can be obtained in approximately 50 to 60% of patients treated with HDCT. Our experience reports the efficacy and safety of HDCT followed by ASCT in relapsed GCT.Methods Analysis of patient records (2012–2019) showed that three patients had received HDCT and ASCT.Results All the three patients were treated with BEP (bleomycin, etoposide, and cisplatin) as first-line therapy. HDCT was done in Case 1 after third-line salvage and in other two patients after second-line salvage chemotherapies. High-dose carboplatin and etoposide were used as conditioning regimen. Granulocyte colony-stimulating factor was used for the mobilization of stem cells. After ASCT, complete remission was documented in all the patients. All were alive and disease-free till the last follow-up. Grade ¾ toxicities including myelosuppression, diarrhea, and mucositis were observed in all three patients.Conclusion This is the first report from India on HDCT with ASCT in GCT. HDCT/ASCT seems to be feasible, safe, and effective in relapsed testicular GCTs.
Keywords: relapsed germ cell tumor; autologous stem cell transplant; high-dose chemotherapy; high-dose carboplatin and etoposide; long-term survival in relapsed GCT